Investment Concepts Introduction to Children through Interactive Videos and Games - Damayanti Damayanti (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2022)
Children will almost certainly need to make investment decisions at some point in their adulthood, no matter their financial status, so they need to learn about investment concepts from a young age to make the right decisions as adults later in life. The community service program's purpose was to introduce children to investment concepts and knowledge. It was intended for students at Madrasah Diniyah Nurriyatul Ulum in Pedak Village, Sulang District, Rembang Regency. The school curriculum had not introduced much, let alone taught about investment concepts. The student's knowledge of investment concepts and knowledge was insufficient. The program offered was aimed at teaching the students about investment concepts and knowledge designed for fifth-grade students. It employed interactive videos and games to improve their soft skills.